Integrating STP and Marketing Mix (4P) for Effective Storytelling Content Development for the Avoskin’s Brand on Instagram - Apriana, Ayu; Wibowo, Sampurno; Cahyani, Leni (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Technological developments demand a more personalized marketing approach for Generation Z. Creating Storytelling Content on Instagram is an effective strategy for building emotional bonds, but its success depends heavily on the alignment of Segmenting, Targeting, Positioning (STP) and Marketing Mix (4P) strategies with audience preferences to prevent message gaps. Therefore, this study aims to determine the relationship between STP and Marketing Mix on the creation of Storytelling Content on Avoskin’s's Instagram social media. This study uses a quantitative approach with a data collection method through the distribution of online questionnaires to 105 respondents who are Avoskin’s's Instagram followers. Sampling was carried out using a purposive sampling technique. The collected data were then analyzed using descriptive statistical analysis methods and multiple linear regression with the help of IBM SPSS software tools. The results of the study prove that the STP and Marketing Mix variables partially and simultaneously have a positive and significant relationship on the creation of Storytelling Content. Together, the two independent variables contribute 86.7% to Storytelling Content. In conclusion, the integration of targeted STP mapping as a narrative foundation and the implementation of the right Marketing Mix has proven to be crucial in creating digital marketing content that is adaptive, interactive, and relevant to the target market.